FRIEND Engine Framework: a real time neurofeedback client-server system for neuroimaging studies - Basilio, Rodrigo; Garrido, Griselda J.; Sato, João R.; Hoefle, Sebastian; Melo, Bruno R. P.; Pamplona, Fabricio A.; Zahn, Roland; Moll, Jorge (Frontiers in Behavioral Neuroscience, 2015)
In this methods article, we present a new implementation of a recently reported FSL-integrated neurofeedback tool, the standalone version of "Functional Real-time Interactive Endogenous Modulation and Decoding" (FRIEND). We will refer to this new implementation as the FRIEND Engine Framework. The framework comprises a client-server cross-platform solution for real time fMRI and fMRI/EEG neurofeedback studies, enabling flexible customization or integration of graphical interfaces, devices and data processing. This implementation allows a fast setup of novel plug-ins and frontends, which can be shared with the user community at large. The FRIEND Engine Framework is freely distributed for non-commercial, research purposes.